Structured object-oriented formal language and method : 6th International Workshop, SOFL+MSVL 2016, Tokyo, Japan, November 15, 2016, Revised selected papers /: 6th International Workshop, SOFL+MSVL 2016, Tokyo, Japan, November 15, 2016, Revised selected papers. (2017) - Unknown
No abstract available